2006
DOI: 10.1116/1.2194023
|View full text |Cite
|
Sign up to set email alerts
|

Detecting free radicals during the hot wire chemical vapor deposition of amorphous silicon carbide films using single-source precursors

Abstract: A vacuum ultraviolet single photon ionization technique has been used to probe gas-phase species important in the hot wire chemical vapor deposition (HW-CVD) of amorphous silicon carbide(a-SiC:H) films using different single-source precursors. This study focuses on monomethylsilane, dimethylsilane, trimethylsilane, tetramethylsilane, and 1,1-dimethyl-1-silacyclobutane, and the reactions of these precursors on tungsten and rhenium filaments between 1000 and 1950°C. Silane is also considered for comparison. Si r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
20
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 39 publications
8
20
0
Order By: Relevance
“…The analysis of gas-phase chemical species generated from the thermal decomposition of TMS in the reactor during the growth process of SiC films by RTCVD [5] indicated that TMS dissociated into hydrogen, silicon atoms, and hydrocarbons such as CH 4 , C 2 H 2 , and C 2 H 4 at the growth temperatures of 1000-1100 • C and a growth pressure of 1 × 10 −4 Torr. In their work on studying the gas-phase species from reactions of methylsilanes, including mono-, di-, tri-and tetra-methylsilane, on tungsten and rhenium filaments in the HWCVD process of silicon carbide films [13], Zaharias et al detected methyl and Si atoms as the products from tetramethylsilane decomposition when the chamber pressure was 5 × 10 −6 Torr. Typical deposition pressures for SiC films using HWCVD or PECVD with either gaseous mixtures of silane and hydrocarbons or single source precursors such as methylsilane range from 0.1 Torr to several Torr [2,3,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of gas-phase chemical species generated from the thermal decomposition of TMS in the reactor during the growth process of SiC films by RTCVD [5] indicated that TMS dissociated into hydrogen, silicon atoms, and hydrocarbons such as CH 4 , C 2 H 2 , and C 2 H 4 at the growth temperatures of 1000-1100 • C and a growth pressure of 1 × 10 −4 Torr. In their work on studying the gas-phase species from reactions of methylsilanes, including mono-, di-, tri-and tetra-methylsilane, on tungsten and rhenium filaments in the HWCVD process of silicon carbide films [13], Zaharias et al detected methyl and Si atoms as the products from tetramethylsilane decomposition when the chamber pressure was 5 × 10 −6 Torr. Typical deposition pressures for SiC films using HWCVD or PECVD with either gaseous mixtures of silane and hydrocarbons or single source precursors such as methylsilane range from 0.1 Torr to several Torr [2,3,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In the decomposition of H 2 O, the production of OH and H is major at low catalyst temperatures, but H and O production becomes more dominant at high temperatures [37]. As for organosilicon compounds, selective and efficient decomposition is possible [51][52][53][54][55][56][57]. The decomposition paths are different from those in thermal decomposition.…”
Section: Discussion and Future Prospectsmentioning
confidence: 96%
“…The reactivity of silacyclobutanes in thermal and photochemical reactions is related to the ring strain in these molecules [10]. The high ring strain energies also lead to reduced decomposition temperatures in the process of chemical vapor deposition, making these molecules excellent choices as single-source precursors for producing silicon carbide thin films [11][12][13][14][15][16]. The strain energy in a four-membered ring structure is closely related to the planarity of the small ring or the extent to which the ring is puckered.…”
Section: Introductionmentioning
confidence: 97%